A Single Haplotype of IFNG Correlating With Low Circulating Levels of Interferon-γ Is Associated With Susceptibility to Cutaneous Leishmaniasis Caused by Leishmania guyanensis - da Silva, George A V; Mesquita, Tirza G; Souza, Victor C; Junior, José do Espírito Santo; Gomes de Souza, Mara Lúcia; Talhari, Anette Chrusciak; Talhari, Sinésio; Naveca, Felipe G; Ramasawmy, Rajendranath (Clinical infectious diseases, 2020)
Abstract Background Interferon-γ (IFN-γ) plays an important role in the control of Leishmania infection. Blockade of IFN-γ signaling in mice increases lesion size and parasite load. In endemic areas of Leishmaniasis, only a fraction of the population develop the disease. This suggest that host genetics may play a role in this response. We investigated whether single nucleotide polymorphisms (SNPs) in IFNG may be associated with elevated or decrease risk in the development of cutaneous leishmaniasis (CL). Methods We assessed 9 SNP and cytosine-adenine (CA) repeats in IFNG by nucleotide sequencing in 647 patients with CL caused by Leishmania guyanensis and 629 controls. Circulating plasma IFN-γ levels were also assayed in 400 patients with CL and 400 controls. Results The rs2069705TT genotype is associated with elevated risk of developing CL compared with the rs2069705CC genotype (OR, 1.7; 95% CI, 1.3–2.4; P = .0008). There is a 70% chance that this genotype raises the risk of developing CL. In a dominant model, carriers of the rs2069705T allele compared with the rs2069705CC genotype showed a 50% (range, 20–100%) increased risk of developing CL (OR, 1.5; 95% CI, 1.2–2.0; P = .0004). Haplotype analysis showed 1 haplotype (H1) associated with low levels of IFN-γ presented an increased risk of 60% of developing CL (OR, 1.6; 95% CI, 1.3–1.9; P = 5 × 10−5) compared with non-H1. Conclusions IFNG variant rs2069705 seems to be a genetic modifier of clinical outcome of Leishmania infection; individuals with the H1 haplotype, associated with low levels of IFN-γ, have a 60% risk of developing CL. Ten polymorphisms covering the interferon-γ gene were assessed in patients with cutaneous leishmaniasis. The study reveals that the polymorphism rs2069705 and 1 haplotype associated with circulating interferon-γ are associated with the development of cutaneous leishmaniasis caused by Leishmania guyanensis.